Construction and initial validation of the E-Work Life Scale to measure remote e-working. Issue 1 (30th October 2018) - Grant, Christine Anne; Wallace, Louise M.; Spurgeon, Peter C.; Tramontano, Carlo; Charalampous, Maria
Abstract : Purpose: The purpose of this paper is to develop and provide initial validation for the new E-Work Life (EWL) Scale. This measure assesses a range of theoretically relevant aspects of the e-working experience related to four main areas: job effectiveness, relationship with the organisation, well-being and work-life balance. Design/methodology/approach: This study presents structured item development. Internal validity and reliability were tested on a sample of 260 e-workers (65 per cent female, age range 25–74). Correlations of the EWL scale with a measure of general health were tested on a subsample of 119 workers to provide initial evidence of construct validity. Findings: Exploratory factor analysis supported a 17-item scale assessing four factors: work-life interference, productivity, organisational trust and flexibility. Individual well-being was measured and a pattern of significant correlations against four factors as indicators of general health were found, including mental health and vitality. Research limitations/implications: A new sample would confirm the strength of the EWL scale alongside further tests of validity. Coping strategies related to the scale would aid mapping of individual competencies for remote e-working to promote e-workers' self-management, management style and organisational policy. Practical implications: The EWL scale helps organisations to evaluate and support the well-being of remote e-workers. It provides measurement on three levels: individual, supervisory and organisational, whereby practical strategies for improvement can be linked to the scale. Originality/value: The EWL scale completes a gap in the research by providing a measure aiding organisations to evaluate and support remote e-worker well-being.